2021
DOI: 10.1186/s13034-021-00381-7
|View full text |Cite
|
Sign up to set email alerts
|

Reasonable suspicion in reporting child maltreatment: a survey among German healthcare professionals

Abstract: Background With regular contacts to the general child population, healthcare professionals could play an important role in the detection of child maltreatment. However, a majority of child maltreatment cases go unnoticed by the healthcare system. Child protection legislations usually offer terms like “reasonable suspicion” to corner a threshold that warrants reporting to child protection services (CPS) is defined as. The indistinct legal terminology leads to marked differences in the interpreta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…Mangelndes Wissen zu Hinweiszeichen, zum Erkennen von Kindesmisshandlung ist ein möglicher Faktor. Auch wenn davon ausgegangen wird, dass nicht alle Formen von Gewalt an Kindern und Jugendlichen durch Fachkräfte im Gesundheitswesen erkannt werden können, ist dennoch davon auszugehen, dass verbesserte Schulung und mehr Kenntnisse zum Kinderschutz zu verbessertem Erkennen beitragen können [31,32]. Weiter deuten aber Aussagen von Experten darauf hin, dass nicht in allen Fällen, wo Kindesmisshandlung durch Fachpersonen im Gesundheitswesen erkannt wird, diese auch dokumentiert wird [6].…”
Section: Analyse Und Ergebnisseunclassified
“…Mangelndes Wissen zu Hinweiszeichen, zum Erkennen von Kindesmisshandlung ist ein möglicher Faktor. Auch wenn davon ausgegangen wird, dass nicht alle Formen von Gewalt an Kindern und Jugendlichen durch Fachkräfte im Gesundheitswesen erkannt werden können, ist dennoch davon auszugehen, dass verbesserte Schulung und mehr Kenntnisse zum Kinderschutz zu verbessertem Erkennen beitragen können [31,32]. Weiter deuten aber Aussagen von Experten darauf hin, dass nicht in allen Fällen, wo Kindesmisshandlung durch Fachpersonen im Gesundheitswesen erkannt wird, diese auch dokumentiert wird [6].…”
Section: Analyse Und Ergebnisseunclassified
“…Previous studies included reports from Germany, Sweden, and Australia, which can be compared with the results of this study. Berthold et al (2021) reported a survey of 2485 physicians and psychotherapists treating children and adolescents in Germany regarding suspicion of child abuse and notification to the CPS [12]. The probability of reporting to the CPS increased positively with the degree of suspected abuse.…”
Section: Notifying the Cgc/womentioning
confidence: 99%
“…However, even when participants had a high degree of certainty that child abuse had occurred, approximately 20% did not choose to notify the CPS. When that certainty was medium, approximately 35% did not choose to report to the CPS [12]. Talsma et al (2015) surveyed general practitioners in Sweden regarding notification of child abuse cases to the CPS.…”
Section: Notifying the Cgc/womentioning
confidence: 99%
See 2 more Smart Citations